Optimalisasi Kemampuan Berpikir Kritis melalui Kombinasi Model Problem Based Learning dengan Flipped Learning - Ni Luh Putu Bagiani; Ketut Agustini; Kadek Suartama (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
Critical thinking is a key component of student competency profiles, yet research indicates that students’ critical thinking skills remain underdeveloped. This study aims to explore and describe the effect of combining Problem-Based Learning (PBL) with Flipped Learning (FL) on optimizing students' critical thinking abilities. A Systematic Literature Review (SLR) was conducted using the PRISMA protocol. Through a structured search strategy, 200 articles published between 2021 and 2025 were identified, from which 22 were selected based on their relevance to the research topic. The highest number of studies on the combination of PBL and FL appeared in 2023 across various educational levels, except early childhood education. Most of the research focused on the influence of this model on students’ critical thinking skills in science and mathematics subjects. The findings indicate that the implementation of PBL combined with FL positively influences students’ critical thinking skills from primary to higher education, especially in exact disciplines. However, its application in non-exact disciplines remains limited, indicating opportunities for future research to explore the potential of this combined model across a wider range of subject areas.